Rising Populism in Global Politics: Causes, Consequences, and Potential Solutions - Wahyu, Firi Pebriani; Aeni, Reni Qurotti (UIN Sunan Gunung Djati Bandung, 2023)
This article delves into the phenomenon of rising populism in global politics, offering a comprehensive examination of its causes, consequences, and potential solutions. Populism, characterized by its appeal to the sentiments and concerns of ordinary citizens, has gained significant traction in various regions around the world. By exploring the underlying drivers, such as economic inequality, cultural shifts, and the erosion of trust in traditional political institutions, we aim to shed light on the roots of this trend. Furthermore, we analyze the far-reaching consequences of populism, including its impact on democratic norms, international relations, and policy outcomes. Lastly, this article outlines potential strategies and solutions for addressing the challenges posed by populism, emphasizing the importance of fostering inclusive political discourse, reinforcing democratic institutions, and promoting evidence-based policymaking. In an era marked by populist surges, this research provides valuable insights for policymakers, scholars, and citizens alike, aiming to contribute to a more informed and constructive dialogue on the future of global politics.